2009
DOI: 10.1159/000200080
|View full text |Cite
|
Sign up to set email alerts
|

<i>Xenopus</i> W-Linked DM-W Induces <i>Foxl2</i> and <i>Cyp19</i> Expression during Ovary Formation

Abstract: The molecular mechanisms of vertebrate ZZ/ZW-type sex-determining systems remain unclear. We recently indicated that a W-linked gene, DM-W is a likely ovary-determining gene in Xenopus laevis. We first examined whether Cyp19 for estrogen-synthesizing enzyme P450 aromatase and Foxl2 showed female-specific expression in developing gonads. Both genes showed much higher expression in ZW than in ZZ gonads during and after sex determination. Importantly, transgenic ZZ gonads expressing exogenous DM-W at the sex-dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…5A), estrogen probably acts downstream of DM-W in the normal ovary-formation cascade. In fact, we recently showed that ectopic DM-W upregulates the expression of Cyp19, which encodes the estrogensynthesizing enzyme P450 aromatase, and of Foxl2 in ZZ gonads (Okada et al, 2009). DMRT1 may directly decrease Foxl2 and/or Cyp19 expression as a repressor, or indirectly as an activator of another factor, in ZW gonads; in either case, DM-W may function to antagonize this activity.…”
Section: Research Article Dmrt1/dm-w In Xenopus Sex Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…5A), estrogen probably acts downstream of DM-W in the normal ovary-formation cascade. In fact, we recently showed that ectopic DM-W upregulates the expression of Cyp19, which encodes the estrogensynthesizing enzyme P450 aromatase, and of Foxl2 in ZZ gonads (Okada et al, 2009). DMRT1 may directly decrease Foxl2 and/or Cyp19 expression as a repressor, or indirectly as an activator of another factor, in ZW gonads; in either case, DM-W may function to antagonize this activity.…”
Section: Research Article Dmrt1/dm-w In Xenopus Sex Determinationmentioning
confidence: 99%
“…In X. laevis, we showed that DM-W is expressed transiently during sex determination, and that some transgenic ZZ tadpoles carrying DM-W expression vectors have primary ovarian structures (Yoshimoto et al, 2008). Moreover, exogenous DM-W in ZZ gonads upregulates the expression of at least two ZW gonad-specific genes, Foxl2 and the aromatase gene Cyp19, during and after sex determination (Okada et al, 2009). These results suggest that the W-linked DM-W is a candidate for a sex (ovary)-determining gene for the ZZ/ZW-type system in X. laevis.…”
Section: Introductionmentioning
confidence: 97%
“…In this frog species, both genetic and phenotypic sex can be determined [Miura et al, 1998], and gene expression levels in differentiating GMCs can be studied separately in genetic males and females. GMC gene expression patterns during sex differentiation have only been studied in a few other frog species, including Xenopus laevis [Semba et al, 1996;Koyano et al, 1997;Takase et al, 1999;Nakajima et al, 2000;Kawano et al, 2001;Lutz et al, 2001;Akatsuka et al, 2005;Osawa et al, 2005;Yoshimoto et al, 2006Yoshimoto et al, , 2008Urbatzka et al, 2007Urbatzka et al, , 2010Okada et al, 2009], Silurana ( Xenopus) tropicalis [El Jamil et al, 2008a;Duarte-Guterman and Trudeau, 2011], Engystomops ( Physalaemus) pustulosus [Duarte-Guterman et al, 2012] or Lithobates catesbeianus (formerly Rana catesbeiana ) [Mayer et al, 2002]. In these reports, 3 genes have consistently exhibited sexually dimorphic expression patterns in gonads of adult frogs and differentiating tadpoles.…”
mentioning
confidence: 99%
“…Nevertheless, evidence is accumulating to suggest that FOXL2 is an important ovarian differentiating gene. Indeed, its ovarian-specific expression is conserved in all vertebrate species studied until now [Loffler et al, 2003;Baron et al, 2004;Govoroun et al, 2004;Wang et al, 2004;Nakamoto et al, 2006;Liu et al, 2007;Rhen et al, 2007;Wotton et al, 2007;Alam et al, 2008;Ijiri et al, 2008;Oshima et al, 2008;Siegfried and Nusslein-Volhard, 2008;Nakamoto et al, 2009;Okada et al, 2009;Shi et al, 2009;Amberg et al, 2010;Moore et al, 2010;Shoemaker-Daly et al, 2010;Wu et al, 2010], and in an invertebrate species such as the pacific oyster [Naimi et al, 2009]. In addition to the function of Foxl2 in development, Foxl2 is also required for ovarian homeostasis.…”
mentioning
confidence: 99%